Epidemiologic Investigation of a Cluster of Neuroinvasive Bacillus cereus Infections in 5 Patients With Acute Myelogenous Leukemia. (1st July 2015) - Rhee, Chanu; Klompas, Michael; Tamburini, Fiona B.; Fremin, Brayon J.; Chea, Nora; Epstein, Lauren; Halpin, Alison Laufer; Guh, Alice; Gallen, Rachel; Coulliette, Angela; Gee, Jay; Hsieh, Candace; et al.
Abstract: Background. Five neuroinvasive Bacillus cereus infections (4 fatal) occurred in hospitalized patients with acute myelogenous leukemia (AML) during a 9-month period, prompting an investigation by infection control and public health officials. Methods. Medical records of case-patients were reviewed and a matched case-control study was performed. Infection control practices were observed. Multiple environmental, food, and medication samples common to AML patients were cultured. Multilocus sequence typing was performed for case and environmental B cereus isolates. Results. All 5 case-patients received chemotherapy and had early-onset neutropenic fevers that resolved with empiric antibiotics. Fever recurred at a median of 17 days (range, 9–20) with headaches and abrupt neurological deterioration. Case-patients had B cereus identified in central nervous system (CNS) samples by (1) polymerase chain reaction or culture or (2) bacilli seen on CNS pathology stains with high-grade B cereus bacteremia. Two case-patients also had colonic ulcers with abundant bacilli on autopsy. No infection control breaches were observed. On case-control analysis, bananas were the only significant exposure shared by all 5 case-patients (odds ratio, 9.3; P = .04). Five environmental or food isolates tested positive for B cereus, including a homogenized banana peel isolate and the shelf of a kitchen cart where bananas were stored. Multilocus sequence typing confirmed that all case and environmental strains were genetically distinct. Multilocus sequence typing-based phylogenetic analysis revealed that the organisms clustered in 2 separate clades. Conclusions. The investigation of this neuroinvasive B cereus cluster did not identify a single point source but was suggestive of a possible dietary exposure. Our experience underscores the potential virulence of B cereus in immunocompromised hosts.